Impact of general vs. neuraxial anesthesia on neonatal outcomes in non-elective cesarean sections - Cocchi, Enrico; Pini, Rita; Gallipoli, Antonella; Stella, Marcello; Antonazzo, Patrizio; Marchetti, Federico; Agnoletti, Vanni (Frontiers in Pediatrics, 2025)
BackgroundCesarean section is a common surgical procedure, usually performed under neuraxial anesthesia and, more rarely, under general anesthesia. The choice of anesthesia in cesarean sections can significantly influence neonatal outcomes, especially in urgent and emergency cases. Previous studies have shown mixed results, often confounded by the inclusion of both elective and emergency cesarean section cases, varying statistical methods, and a focus solely on resuscitation immediate-term neonatal outcomes.ObjectiveThis study aims to use robust statistical methods to evaluate the impact of anesthesia type on immediate and longer-term neonatal outcomes in urgent and emergency cesarean section cases, where additional detrimental factors might influence this relationship.MethodsWe analyzed 395 women who underwent non-elective cesarean sections between 2021 and 2023. Inverse probability of treatment weighting (IPTW) served to focus on the role of anesthesia type eliminating confounding variables effect, in simulated randomized controlled trial conditions.ResultsGeneral anesthesia increases odds of neonatal resuscitation (OR 6.1, p < 0.001), NICU admission (OR 1.8, p: 0.04), and a 15% lower Apgar score at 1 min (p: 0.02). General anesthesia also increased NICU admission rate for respiratory insufficiency (OR 7.6, p < 0.001), the need for oxygen (OR 4.8, p: 0.003) and CPAP (OR 3.6, p < 0.001) in NICU. Negative controls and consistent sensitivity analyses further validated the robustness of our findings.ConclusionGeneral anesthesia in non-elective cesarean sections is associated with worse neonatal outcomes, extending beyond the resuscitation phase to sustained NICU morbidity. Our study provides novel insights into the specific neonatal resuscitation maneuvers required when general anesthesia is used, enhancing clinicians preparedness for managing high-risk deliveries. These findings underscore the critical importance of anesthesia choice, advocate for the preference of neuraxial techniques, and highlight the need for further research into long-term neonatal outcomes.